Pilot-Scale Testing of UV-A Light Treatment for Mitigation of NH3, H2S, GHGs, VOCs, Odor, and O3 Inside the Poultry Barn - Lee, Myeongseong; Li, Peiyang; Koziel, Jacek A.; Ahn, Heekwon; Wi, Jisoo; Chen, Baitong; Meiirkhanuly, Zhanibek; Banik, Chumki; Jenks, William S. (Frontiers in Chemistry, 2020)
Poultry farmers are producing eggs, meat, and feathers with increased efficiency and lower carbon footprint. Technologies to address concerns about the indoor air quality inside barns and the gaseous emissions from farms to the atmosphere continue to be among industry priorities. We have been developing and scaling up a UV air treatment that has the potential to reduce odor and other gases on the farm-scale. In our recent laboratory-scale study, the use of UV-A (a less toxic ultraviolet light, a.k.a. ‘black light’) and a special TiO2-based photocatalyst reduced concentrations of several important air pollutants (NH3, CO2, N2O, O3) without impact on H2S & CH4. Therefore, the objectives of this research were to (1) scale-up of the UV treatment to pilot-scale, (2) evaluate the mitigation of odor and odorous VOCs, and (3) complete preliminary economic analyses. A pilot-scale experiment was conducted under commercial poultry barn conditions to evaluate photocatalyst coatings on surfaces subjected to UV light under field conditions. In this study, the reactor was constructed to support interchangeable wall panels and installed on a poultry farm. The effects of a photocatalyst’s presence (photocatalysis & photolysis), UV intensity (LED & fluorescent), and treatment time we studied in the pilot-scale experiments inside a poultry barn. The results of pilot-scale experiments were consistent with the lab-scale: the % reduction under photocatalysis was generally higher than photolysis. In addition, the % reduction of target gases at a high light intensity and long treatment time was higher. The % reduction of NH3 was 5~9%. There was no impact on H2S, CH4, and CO2 under any experimental conditions. N2O & O3 concentrations were reduced at 6~12% & 87~100% by both photolysis & photocatalysis. In addition, concentrations of several VOCs responsible for livestock odor were reduced from 26~62% and increased with treatment time & light intensity. The odor was reduced by 18%. Photolysis treatment reduced concentrations of N2O, VOCs, and O3, only. The initial economic analysis has shown that LEDs are more efficient than fluorescent lights. Further scale-up and research at farm-scale are warranted.